Effects of stress on school bullying behavior among secondary school students: Moderating effects of gender and grade level - Luo, Siliang; Ban, Yongfei; Qiu, Tianlong; Liu, Changyou (Frontiers in Psychology, 2023)
This study investigated the effects of stress on school bullying behaviors among middle school students, and the moderating role of gender and grade level in this relationship. To this end, the OBVQ secondary school version of the Child Bullying Questionnaire and the Stressor Scale for Secondary School Students were used to survey 3,566 secondary school students in Guizhou Province, and the data were statistically analyzed. Results showed that stress was significantly and positively associated with school bullying among secondary school students. Furthermore, both gender and grade moderated the relationship between stress and school bullying, showing that boys and middle school children are more likely to engage in bullying than girls and high school students, respectively. The results of the study provide a theoretical basis for the prevention and intervention of school bullying behaviors among middle school students.